Selected glass finds from Apsorus (Osor) - reflection of wealth and prestige - Lazar, Irena (Studia universitatis hereditati, 2025)
The article focuses on selected glass finds from Osor. The exact provenance of the finds is unknown; most likely, they were discovered in a Roman necropolis of Apsorus. Among the excavated materials, early products of Roman glassmaking, dated to the 1st century AD, stand out and illustrate the remarkable diversity of glassmaking technological practices of the period. Some of them were still made in moulds, others by mould-blowing, but we should also mention the earliest blown products. Imports of these products in Roman towns and cities along the Adriatic reflect the economic strength of the population and an extensive trade network expanding from northern Italy to the Eastern Mediterranean.
Keywords: import; kalupi in pihanje v kalup; moulds and mould-blowing; Osor; rimsko steklo; Roman glass; trade; trgovina; uvoz